2022
DOI: 10.1186/s40729-022-00443-1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous placement of short implants (≤ 8 mm) versus standard length implants (≥ 10 mm) after sinus floor elevation in atrophic posterior maxillae: a systematic review and meta-analysis

Abstract: Purpose The objective of this meta-analysis was to compare the clinical outcomes of using short implants (≤ 8 mm) inserted with osteotome sinus floor elevation (OSFE) and standard implants (≥ 10 mm) inserted with sinus floor elevation (SFE) in atrophic posterior maxillae with insufficient residual bone height (RBH). Methods An electronic search was performed on PubMed, EMBASE, and the Cochrane Library from 1994 to July 2022, in combination with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Meta‐regression analysis was performed to evaluate the influence of implant length on the implant survival and there was no significant difference between short and long implant groups in TSFA. These results were in agreement with previous systematic review, showing the similar implant survival of short implants combined with TSFA to the long implants with TSFA (Lin et al, 2021) or SFA (Tang et al, 2022), but these findings were obtained from the sites with RBH <8 mm. The short implant can reduce the possibility of intraoperative complications and simplify the surgery procedures of implant placement, but too short implants may impact the normal crown‐implant ratio and functional reliability.…”
Section: Discussionsupporting
confidence: 93%
“…Meta‐regression analysis was performed to evaluate the influence of implant length on the implant survival and there was no significant difference between short and long implant groups in TSFA. These results were in agreement with previous systematic review, showing the similar implant survival of short implants combined with TSFA to the long implants with TSFA (Lin et al, 2021) or SFA (Tang et al, 2022), but these findings were obtained from the sites with RBH <8 mm. The short implant can reduce the possibility of intraoperative complications and simplify the surgery procedures of implant placement, but too short implants may impact the normal crown‐implant ratio and functional reliability.…”
Section: Discussionsupporting
confidence: 93%
“…This has been observed by other authors such as Akca et al [ 39 ], who reported that bone quality had more influence than implant shape. This could be explained considering that PS depends on implant-bone contact in the cortical part, so length should not be a factor that influences ISQ [ 40 , 41 ]. More authors have compared different techniques and have related them to the macrodesign of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…Placement of short implants is associated with a reduced bone-to-implant contact and increased crown-to-implant ratio compared with placement of standard-length implants, which could lead to an increased risk of implant failure or loss. Systematic reviews comparing implant treatment outcomes following prosthetic rehabilitation of the atrophic posterior maxilla with short implant compared with sinus floor augmentation and standard-length implants have demonstrated comparable implant survival rates, risk of complications, and patient satisfaction [64][65][66][67][68][69][70][71]. However, the conclusions of the systematic reviews should be interpreted with caution due to study heterogeneity involving short implants with different lengths, comparison of splinted and non-splinted prosthetic solutions, and dissimilar observation periods.…”
Section: Sinus Floor Augmentation and Standard-length Implants Versus...mentioning
confidence: 99%